Laterality effects in the spinning dancer illusion: The viewing‐from‐above bias is only part of the story. (15th December 2015) - Lucafò, Chiara; Marzoli, Daniele; Prete, Giulia; Tommasi, Luca
Abstract : The 'silhouette illusion', representing the silhouette of a female dancer pirouetting about her vertical axis, is a bistable stimulus created by Japanese web designer Nobuyuki Kayahara. Although the dancer can be perceived as spinning either clockwise or counterclockwise, the clockwise rotation is usually preferred. Troje and McAdam ( i‐Perception, 2010, 1, 143) showed that this clockwise bias can be attributed to the tendency to assume a viewpoint from above rather than from below, given that the dancer is portrayed from a vantage point that is not perpendicular to the axis of rotation. Here, we tested whether another possible factor contributing to the observers' interpretation of this bistable stimulus might be the tendency to perceive movements of the right rather than the left foot. We confirmed both the viewing‐from‐above bias and our hypothesis. The bias to perceive movements of the right leg might be a generalization to lower limbs of a perceptual frequency effect already observed for upper limbs. Such a perceptual and attentional bias towards the right hand/foot could account for the greater ability to predict the outcome of sport actions when observing right‐ rather than left‐limbed movements, and thus the left‐handers' and left‐footers' advantage observed in a variety of interactive sports.